METAL AND COLLOIDAL CLAY REMOVAL TECHNOLOGY IN OPEN-CAST COAL MINE WATER: COMPARISON OF CHEMICAL COAGULATION AND ELECTROCOAGULATION - Hasan, Faiz
Mining operations are carried out by digging and transporting overburden material in relatively large amounts. These activities can have potential environmental impacts, especially related to water management. Coal mine water tends to have colloidal characteristics with a clay composition that is difficult to settle. This study aims to determine coal mine water characteristics and the potential application of wastewater treatment technology through chemical coagulation and electrocoagulation processes. Chemical coagulation was carried out using alum and PAC at a dose range of 140 - 400 mg/L, while electrocoagulation was carried out with 15 liter continuous flow reactor with aluminum electrodes (Current Intensity 6A; 0.3 LPM). Laboratory tests on the liquid and solid phase were carried out for physical, chemical and metal parameters before and after the mine water treatment. The coal mine water sample is categorized as neutral mine water, specifically sodium-bicarbonate mine water. Suspended solids with size of 1862.5 nm were observed using LR-TEM with zeta potential value of -20.9 mV. The dominant minerals contained in the mine water are kaolinite (62.4%) and quartz (25.9%). Removal of suspended solids using chemical coagulation can reach up to 96% at a dose of 230 mg alum/L, meanwhile with electrocoagulation process can reach up to 98% removal of suspended solids. Characterization and understanding of chemical coagulation and electrocoagulation processes are expected to provide a basis for determining effective mine water treatment methods in coal mining operation.